Serological survey of the infection of parainfluenzavirus type 3 in cattle in Malatya - Özdarendeli, A; Kandil, M (Scientific Technical Research Council Turkey, 2001)
Cattle serum samples were examined for antibodies to parainflue nza type 3 (PI-3) virus using the hemaglutination-inhibition (HI) test. These sera were taken in autumn 1994 and spring 1995 from clinically healthy cattle in Malatya. Antibodies to PI-3 virus were detected in 897 out of 1000 cattle sera 89.7%. Reciprocal antibody titres to PI-3 virus in cattle ranged from 1:16 to 1:1024. It was determined that the proportion of seropositive sera in the cattle in the spring was higher than in the autumn.
Keywords: cattle; parainfluenzavirus type 3; HI-antibodies